2021
DOI: 10.1136/bmjgh-2021-007282
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pulse oximetry on diagnosis, management and outcomes of acute febrile illness in low-income and middle-income countries: a systematic review

Abstract: BackgroundAcute fever is a common presenting symptom in low/middle-income countries (LMICs) and is strongly associated with sepsis. Hypoxaemia predicts disease severity in such patients but is poorly detected by clinical examination. Therefore, including pulse oximetry in the assessment of acutely febrile patients may improve clinical outcomes in LMIC settings.MethodsWe systematically reviewed studies of any design comparing one group where pulse oximetry was used and at least one group where it was not. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Pulse oximetry was a core part of risk assessment in most included studies (although two of the earlier RCTs did not include oximetry), identifying severely ill children with hypoxaemia who otherwise may not have been appropriately referred or treated with oxygen. This finding concurs with other studies on pulse oximetry that have found pulse oximetry is an objective measure that improves hypoxaemia detection and risk stratification and provides health care workers and patients/families with greater confidence in treatment plans [ 40 , 44 - 49 ].…”
Section: Discussionsupporting
confidence: 91%
“…Pulse oximetry was a core part of risk assessment in most included studies (although two of the earlier RCTs did not include oximetry), identifying severely ill children with hypoxaemia who otherwise may not have been appropriately referred or treated with oxygen. This finding concurs with other studies on pulse oximetry that have found pulse oximetry is an objective measure that improves hypoxaemia detection and risk stratification and provides health care workers and patients/families with greater confidence in treatment plans [ 40 , 44 - 49 ].…”
Section: Discussionsupporting
confidence: 91%
“…To our knowledge, this is the first study assessing the cost‐effectiveness of pulse oximetry in a LMIC rural primary care setting based on highly granular patient‐level data. We have also investigated the cost‐effectiveness of pulse oximetry in patients older than 5 years, who have not been the focus of previous comparative studies evaluating this intervention [ 17 ]. Additionally, we have factored in the cost of antimicrobial resistance in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Second, because there is a paucity of data on the clinical impact of pulse oximetry in older children and adults in LMICs, we had to extrapolate findings from the literature pertaining to children <5 years old to these patient categories. Third, most data from the literature were derived principally from studies conducted in LMICs outside Southeast Asia, as an extensive systematic review failed to identify relevant studies carried out in this region [ 17 ]. To mitigate this, we have adapted, as far as possible, the potential impacts of pulse oximetry to the socio‐economic conditions in Thailand; for example, it is likely that most patients referred to hospital in Thailand will attend [ 22 ], unlike in many African countries [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another review suggested trends toward fewer ICUs transfers with continuous Sp o 2 compared with spot checks but indicated that capnography may provide earlier warning of respiratory depression (12). Other reviews have highlighted the low level of evidence in support of the use of Sp o 2 and called for more research into optimizing its use, establishing patient-specific thresholds, and creating paradigms that positively improve outcomes across clinical settings (13, 14).…”
Section: Is the Use Of Pulse Oximetry Validated By Evidence-based Med...mentioning
confidence: 99%